Preliminary study on BRICS sequential therapeutic regimen as salvage treatment for refractory advanced colorectal cancer patients harboring pMMR status - Peng, Yonghai; Wang, Jian; Wang, Junhui; Chen, Jianxin (Frontiers in Immunology, 2025)
BackgroundPatients with refractory mismatch repair-proficient/microsatellite stable (pMMR/MSS) metastatic colorectal cancer exhibit intrinsic resistance to immune checkpoint inhibitors and conventional salvage therapies, with median overall survival (OS) is typically less than 10 months. This study evaluates the novel BRICS sequential regimen (Bifidobacterium supplementation, Radiotherapy, Immunotherapy, Chemotherapy, Stereotactic approach) in this population.MethodsIn this retrospective analysis, 27 refractory pMMR/MSS metastatic CRC patients received BRICS: Stereotactic body radiotherapy to a single lesion, indefinite high-dose probiotics, followed by low-dose chemotherapy plus PD-1 inhibitor. Primary endpoints were objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), and OS.ResultsEfficacy outcomes: ORR 33.3% (9 partial responses), DCR 88.9%, median PFS 7.20 months (95% CI: 5.23–9.18), and median OS 12.30 months (95% CI: 9.89–14.71). Eastern Cooperative Oncology Group Performance Status (ECOG PS) >2 independently predicted inferior OS (HR = 4.860; p=0.042), while metastatic burden (≥3 organs) predicted shorter PFS (HR = 3.179; p=0.026). Grade 3–4 adverse events occurred in 22.2% of patients (neutropenia: 14.8%; thrombocytopenia: 3.7%; anemia: 3.7%).ConclusionsBRICS demonstrates clinically meaningful efficacy (DCR 88.9%, mOS 12.3 months) and manageable toxicity in refractory pMMR/MSS metastatic CRC. ECOG PS >2 and high metastatic burden identify patients with limited benefit, warranting prospective validation in biomarker-enriched cohorts.